2021
DOI: 10.1007/jhep04(2021)119
|View full text |Cite
|
Sign up to set email alerts
|

Hairy magnetic and dyonic black holes in the Standard Model

Abstract: Spherically symmetric magnetic and dyonic black holes with a magnetic charge Q = 2 are studied in the Standard Model and general relativity. A magnetically charged black hole with mass below 9.3 × 1035 GeV has a “hairy” cloud of electroweak gauge and Higgs fields outside the event horizon with 1/mW in size. An extremal magnetic black hole has a hair mass of 3.6 TeV, while an extremal dyonic black hole has an additional mass of q2 × 1.6 GeV for a small electric charge q ≪ 2π/e2. A hairy dyonic black hole with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…where n(m 1 , Q 1 ) and n(m 2 , Q 2 ) are the comoving average number density of charged BHs with masses m 1 , m 2 and charges Q 1 , Q 2 , and σv denotes the average over relative velocity distribution with σ = πb 2 max given in Eq. (25). In this section, we have worked out the merging cross section of charged BHs without assuming the origin of those charged BHs.…”
Section: Capturementioning
confidence: 99%
See 1 more Smart Citation
“…where n(m 1 , Q 1 ) and n(m 2 , Q 2 ) are the comoving average number density of charged BHs with masses m 1 , m 2 and charges Q 1 , Q 2 , and σv denotes the average over relative velocity distribution with σ = πb 2 max given in Eq. (25). In this section, we have worked out the merging cross section of charged BHs without assuming the origin of those charged BHs.…”
Section: Capturementioning
confidence: 99%
“…This paramount and non-trivial theorem allows people to reduce all BH solutions to just three physical quantities. Compared to Schwarzschild BHs, charged BHs emit not only gravitational radiation but also electromagnetic radiation, and have attracted much attention [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Recently, assuming that the influence of BH spins can be neglected, Bozzola et al found that the charge-to-mass ratios of up to 0.3 are compatible with Binary BH merger event GW150914 [21].…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate this framework, we explore in this work the case where electroweaksymmetric (EWS) balls act as the catalyst. Such states can arise in many theories, including non-topological solitons [6][7][8], dark monopoles [9], or magnetically charged black holes [10][11][12][13][14]. Schematically, the catalyzed baryogenesis process for this particular catalyst is illustrated in figure 1.…”
Section: Jhep10(2021)147mentioning
confidence: 99%
“…We give brief overviews of two such models here, and full details (including formation mechanisms) can be found in the corresponding references. It is worth mentioning a third possibility for EWS objects is a magnetically charged black hole [12][13][14], but their masses are greater than the Planck scale and thus too heavy to be of interest according to figures 2 and 3.…”
Section: Jhep10(2021)147mentioning
confidence: 99%
“…These objects usually go under the name of hairy magnetic BHs and they have received increased attention in the recent literature (see e.g. [9][10][11][12] and references therein). Given the obvious analogy between vortex and monopole solutions, it seems reasonable to ask whether self-gravitating Abrikosov vortices can also hold a small black hole within their core.…”
Section: Introductionmentioning
confidence: 99%